2007
DOI: 10.1186/1750-9378-2-21
|View full text |Cite
|
Sign up to set email alerts
|

High risk HPV types 18 and 16 are potent modulators of oral squamous cell carcinoma phenotypes in vitro

Abstract: Background: Human papillomavirus (HPV) has been confirmed as the primary etiological factor that transforms cervical epithelia into cancer. The presence of HPV in oral cancers suggests that HPV may play a similar role in transforming the oral epithelia. A high degree of variability in the prevalence of HPV in oral cancers has been found, however, raising questions regarding its role in the transformation and development of oral cancers. The goal of this study was to test our hypothesis that high-risk HPV strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 35 publications
3
28
0
4
Order By: Relevance
“…HPV16 has been considered as the predominant HPV subtype involved in oropharyngeal cancer [9], [10], [12][16], [27]. However, the infection rates for HPV18 were the same as for HPV16 (30.3%) in this study population (Table 1).…”
Section: Discussionmentioning
confidence: 71%
“…HPV16 has been considered as the predominant HPV subtype involved in oropharyngeal cancer [9], [10], [12][16], [27]. However, the infection rates for HPV18 were the same as for HPV16 (30.3%) in this study population (Table 1).…”
Section: Discussionmentioning
confidence: 71%
“…Cell number was determined using Trypan Blue (Fisher Scientific: Fair Lawn, New Jersey, USA) using a Zeiss Axiovert 40 inverted microscope (Carl Ziess, Inc: Thornwood, New York, USA) and a hemacytometer (Fisher Scientific: Fair Lawn, New Jersey, USA). To determine if any samples harbored the HPV virus, DNA was isolated from the saliva sample using a minimum of 3.5 x 10 5 cells using the GenomicPrep DNA isolation kit (Amersham Biosciences: Buckinghamshire, United Kingdom), using the procedure recommended by the manufacturer as previously described [12,42,78,79]. DNA purity was calculated using ratio measurements of absorbance at 260 and 280 nm (A260/A280 ratio between 1.7 and 2.0).…”
Section: Methodsmentioning
confidence: 99%
“…DNA from each sample was then used to perform PCR with the Fisher exACTGene complete PCR kit (Fisher Scientific: Fair Lawn, New Jersey, USA) and a Mastercycler gradient thermocycler (Eppendorf: Hamburg, Germany) using the following primers for HPV16 [12,78], HPV18 [12,78,79], and glyceraldehyde- 3- phosphate dehydrogenase (GAPDH) [80] (SeqWright: Houston, Texas, USA):…”
Section: Methodsmentioning
confidence: 99%
“…The results have shown that HPV could be involved in the onset of certain types of carcinoma. In the last few years, the literature has provided evidence that HPV can be an independent risk factor for squamous cell carcinoma (9,10). Case-control studies such as the one performed in 2008 by Pintos J et al (9), show that infection from highrisk HPV is associated with 19% of cases and 5% of controls.…”
Section: Resultsmentioning
confidence: 99%